2015
DOI: 10.5664/jcsm.5002
|View full text |Cite
|
Sign up to set email alerts
|

Bispectral Index in Evaluating Effects of Sedation Depth on Drug-Induced Sleep Endoscopy: DISE or No Dice

Abstract: British otolaryngologists Pringle and Croft fi rst introduced drug-induced sleep endoscopy (DISE) in 1991 as a technique to identify the anatomic location of obstruction in the airway of patients with snoring and obstructive sleep apnea. 1Since then, DISE, or sleep nasendoscopy, has been widely adopted as a diagnostic tool for dynamic airway evaluation. This technique is complementary to polysomnographic data, as it is used to differentiate the site of obstruction. DISE is commonly utilized to direct subsequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 10 publications
(9 reference statements)
0
4
0
Order By: Relevance
“…Therefore, we thought it reasonable to include lower levels of BIS (40–60) for DISE examination. There have been arguments in the literature that BIS might be ineffective with dexmedetomidine . Kasuya and colleagues found that while comparing propofol and dexmedetomidine in healthy volunteers, BIS values were significantly lower with dexmedetomidine than propofol at the same sedation score .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, we thought it reasonable to include lower levels of BIS (40–60) for DISE examination. There have been arguments in the literature that BIS might be ineffective with dexmedetomidine . Kasuya and colleagues found that while comparing propofol and dexmedetomidine in healthy volunteers, BIS values were significantly lower with dexmedetomidine than propofol at the same sedation score .…”
Section: Discussionmentioning
confidence: 99%
“…In OSA patients, obstruction is more severe in the rapid eye movement phase of sleep, and neither of the study drugs has any effect on rapid eye movement sleep . Second, the use of BIS for monitoring sedation depth with dexmedetomidine still has not been proven . However, there has been recent evidence that a BIS value of 40 to 60 can be used to determine deep sedation depth with dexmedetomidine .…”
Section: Discussionmentioning
confidence: 99%
“…Second, the depth of sleep and wakefulness cannot be assessed effectively in an accurate and consistent way. Based on previous research, adequate depth of sedation and anesthesia for DISE in OSAHS children was UMSS score of 3 or BIS 65–75 in this study ( Stierer and Ishman, 2015 ; Lo et al, 2015 ; Shields et al, 2005 ; Malviya et al, 2002 ). The scores for pediatric awakening depth were very few.…”
Section: Discussionmentioning
confidence: 95%
“…Numerous publications provide evidence that the levels, patterns, and intensity of the collapse of the upper airway can change depending on the depth of sedation. [8][9][10][11] Therefore, it seems appropriate to monitor the depth of sedation during DISE aiming to reach a level of sedation which imitates different sleep stages of natural sleep. BiSpectral Index™ (BIS) is used as a common method for measuring the depth of sedation during DISE.…”
Section: Introductionmentioning
confidence: 99%